Ashtimki among the Tharus: A Study of Celebration of the Ritual in Kailali - Chaudhary, Surya Bahadur (NPRC Journal of Multidisciplinary Research, 2026)
Background: Ashtimki is a ritual festival practiced by Tharu women in Kailali District, Nepal. It is concerned with cultural, social and ethnical norm and values to celebrate Ashtimki as other festivals in Kailali, a district in Nepal's Far Western Province. As a part of ritual practice, the women take fasting on Ashtimki to purify their body and soul through the festival activities. At the present time, it is significant to new generation to preserve and enrich the Tharu culture through this paper.Method: This qualitative study examines Astimki, a ritual festival practiced by boys, girls and women in Kailali. There is no more gender bias because it is believed that male and female have equal rights to celebrate together harmoniously. The research will be based on the field observation and in-depth interview of the respondents, purposively selected for the study has been taken as the source of data. The qualitative data has been interpretated by using theoretical insights from performance studies.Result: The Tharu practitioners take fasting for good health, agriculture, and the well-being of other family members. It is believed that Ashtimki marks the arrival of the new season, and the summer season is over. They get relief from summer diseases. In this festival, the four main ritual activities focus on Agiyara (to worship the fire god), Agrashan (to worship food god and offer to the god before eating) Tika, and Parohana ( to worship the Ganga or water as holy goddess) These rituals are the main parts of Ashtimki, which allow them to confess their past sins.Conclusion: They celebrate other festivals throughout the year in their own way to strengthen and promote their racial and cultural identity, encouraging cooperation among their youth. The paper serves as a model for other researchers. This festival focuses on regional variations in the celebration of Ashtimki.Novelty: It shows the typicality and richness of the culture's and ritual beliefs' practices. Tharus have their own unique ethnicity, culture, festivals, rites and rituals, and household composition. The cultural traditions, art, literature, songs, and festivals of the Tharus reflect their history. The recorded texts of the personal interviews and folk tales also support this fact, and the respondents' opinions on the socio-cultural questions are expressed.